Eksplorasi Kontribusi Ekonomi Indonesia sebagai Negara Global South di Tingkat Global - Rosyida Liviana; Annisa Dewantari; Roby Rakhmadi (Jurnal Terekam Jejak, 2023)
This research discusses the exploration of Indonesia's economic contribution as a Global South country. The study mainly focused on finding out Indonesia's economic contribution at the global level. The study was conducted using qualitative research methods and various secondary sources and official reports from Indonesia’s Ministry of Finance and Ministry of Foreign Affairs. Several instruments were used in the research process, including International Aid Support, positive foreign trade trends, Indonesia's role in South-South cooperation, and participation in relevant G20 forums. The results show that Indonesia already has a strong economy, with a stable trade surplus until 2022, despite the challenges of the COVID-19 pandemic. Indonesia has also emerged as an important economic partner in the Southeast Asian region, and as a Global South country, serving as one of the main representatives in global forums. The findings of this study emphasize Indonesia's important position on the global economic stage, and show that this needs to be understood in relation to the concept of interdependence and the concept of mutual gains through cooperation between countries.